Peningkatan Kinerja Karyawan Melalui Faktor-Faktor Penunjang Kepuasan Kerja Pada Pt. Enggal Jaya Boja Kabupaten Kendal - Mukhlidin, Mukhlidin; Rahmawati, Widya; Yahya, Andi Fauziah (STIE AMKOP, 2024)
This study aims to analyze the effect of motivation and communication on employee performance with job satisfaction as a mediating variable at Enggal Jaya Boja Kendal Company. The research approach used is quantitative with survey method. Data were collected through questionnaires distributed to all company employees. The population of this study were all employees of Enggal Jaya Boja Kendal Company totaling 160 people and the sample used was 160 people. The results showed that motivation and communication have a significant positive effect on employee performance. Job satisfaction is also able to mediate the relationship between motivation and communication with employee performance. This indicates that increasing motivation and effective communication can improve job satisfaction, which in turn has an impact on creating employee performance. Keywords: Motivation, Communication, Job Satisfaction, Employee Performance